Fetal out comes in Pre-Eclampsia with raised Maternal Serum Uric Acid - Afshan Nadeem, Abida Rehman, Nayyer Sultana, Riffat Mehmood, Areysia Merum, Nouman Riaz, Zahid Mehmood (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare adverse fetal outcome of hyperuricemic pre-eclamptic pregnancy with normouricemic pre-eclamptic pregnancy. Study design: A Cohort Study Methodology: In this study patients with serum uric acid level(SUA) >5.5mg/dl were included in group A and patients with SUA level <5.5mg/dl were included in group B. Patients with medical disorders like renal disease, hypertension, diabetes and currently using drugs affecting uric acid levels like thiazide diuretics were excluded. Both groups were followed until delivery. Intrauterine growth restriction, low birth weight was recorded. Results: A total of sixty patients were studied with age range from 18 to less than 40 years. The mean age in group A was 33.566± 4.19 years while 34.100± 3.46 years in group B. Mean Gestational age was 33.500±4.22 weeks in group A and 34.200±4.71 weeks in group B, while mean serum uric acid level was 7.416±1.04 in group A and 4.202±0.61 in group B. Intrauterine growth restriction was seen 93.3% in group A as compare to 60% in group B (P=0.002)(RRR=55.5%) while Low birth weight was 70% in group A and 10% in group B (P=0.000). Conclusion: The pregnancies with pre-eclampsia and raised serum uric acid levels result in adverse fetal outcome. Significant increased number of IUGR and LBW fetuses were observed in babies born to pre-eclamptic mothers with raised serum uric acid levels in comparison with babies born to normo-uricemic pre eclamptic mothers.